Code-Mixing and Code-Switching in the TV Culinary Show MasterChef Indonesia - Yusuf, Muhammad; Gapur, Abdul (International Journal of Culture and Art Studies, 2024)
This research examines the linguistic phenomena of code-mixing and code-switching in Indonesian culinary television programs, focusing on MasterChef Indonesia Season 11. The research identifies the forms of code-mixing, which include inner, outer, and hybrid mixing of languages, as well as different types of code-switching, such as tag switching, inter-sentential switching, and intra-sentential switching. The factors influencing these language shifts include globalization, the influence of foreign cultures, the need for commercial appeal, limitations in Indonesian vocabulary, and the communication habits of individuals in the culinary media. The research reveals that foreign terms, especially English, are commonly used in culinary contexts to describe techniques, ingredients, and concepts without direct Indonesian equivalents. While the use of foreign languages can enrich the Indonesian vocabulary and aid in adapting modern concepts, concerns arise regarding the erosion of the purity of Indonesian and its shifting status concerning global languages. The study underscores the importance of strategic measures for language preservation, including promoting awareness of linguistic identity and enforcing policies that ensure proper Indonesian use in mass media. The findings contribute to a deeper understanding of language dynamics in public television and its potential impact on developing and preserving Indonesian as the national language.